THE EFFECT OF WORK MOTIVATION, TRAINING AND COMPENSATION ON THE EMPLOYEE PERFORMANCE OF MEDIROSSA HOSPITAL 2 BEKASI - Tri Mulyani Kartini; Etty Zuliawati Zed (International Journal of Economics and Management Research, 2022)
This research was conducted to determine the magnitude of the influence between motivation. Work, Training and Compensation for Employee Performance. The number of samples in this study were 67 employees at Medirossa Hospital 2 Bekasi. The sampling method used is nonprobability sampling, with the help of statistical software SPSS version 26. The results of the t-test data processing for the work motivation variable (X1) t count 4.554 > 1.998, with a significance value of 0.000 < 0.05 and the Training Variable t count 5,600 > t table 1.998 with a significance value of 0.00 < 0.05 and compensation (X3) t count -2.582 < 1.998 with a significance value of 0.00 < 0.05 then work motivation and training partially have a significant effect while partial compensation has no effect . The results of the f test data processing with an f table value of 35.806 > F table 3.16 and a significance value of 0.00 < 0.05 then Ho is rejected and H4 is accepted, so that work motivation, training and compensation have a simultaneous effect on employee performance.